تفعيل دور الزكاة في الحد من مشكلة الفقر في ولاية جوزجان بأفغانستان : دراسة تحليلية - عبادي، حسام الدين (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This study attempts to stimulate the role of Zakat in reducing the problem of poverty in Afghanistan in general and in the state of Jowzjan in particular. The problem of poverty is a major problem that threatens many societies with disintegration and breakdown. Zakat plays an important role in reducing poverty, provided that it is paid and distributed according to what is required by Islamic law. The central problem that the researcher seeks to show and treat through a prudent stance is that reducing poverty by activating the role of zakat contributes to treating ignorance and disease. The research discusses first the concept of poverty and its causes and the concept of Zakat and its provisions, and secondly the possibility of applying the legal system of Zakat and its role in the social and economic life in Afghanistan, and finally how the application of the Zakat system contributes to reducing the problem of poverty in the state of Jowzjan, and the consequences that follow. To study these themes, the researcher employed inductive and analytical methods. In addition, interviews were conducted with some economists, Sharia scholars, and tribal leaders responsible for solving the problem of poverty and to enrich the practical aspect of the study. The research concluded a set of results; the most important among them are: Afghanistan is a developing country due to political instability, continued war, and corruption and requires foreign aid. Zakat giving and its good governance will greatly enhance socioeconomic justice, and lead to poverty reduction. Developing Zakat funds by the government based on the model available in the Muslim World will ease Zakat collection and its distribution. Hence, it will reduce poverty, and many issues related to lack of wealth.